2022
DOI: 10.1002/acm2.13738
|View full text |Cite
|
Sign up to set email alerts
|

Robust optimization of VMAT for prostate cancer accounting for geometric uncertainty

Abstract: The aim of this study was to propose optimal robust planning by comparing the robustness with setup error with the robustness of a conventional planning target volume (PTV)-based plan and to compare the robust plan to the PTV-based plan for the target and organ at risk (OAR). Data from 13 patients with intermediate-to-high-risk localized prostate cancer who did not have T3b disease were analyzed. The dose distribution under multiple setup error scenarios was assessed using a conventional PTV-based plan. The cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…In literature, some works were focused on the dosimetric or radiobiological assessment of systematic isocenter shift errors for different types of cancers. [17,18,24]. This work aimed to evaluate both the dosimetric and radiobiological effects of the random setup error that usually occurs during the position of prostate patients.…”
Section: Discussionmentioning
confidence: 99%
“…In literature, some works were focused on the dosimetric or radiobiological assessment of systematic isocenter shift errors for different types of cancers. [17,18,24]. This work aimed to evaluate both the dosimetric and radiobiological effects of the random setup error that usually occurs during the position of prostate patients.…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Several studies have reported on the effectiveness of robust planning. [21][22][23] Miura et al performed robust planning for laryngeal cancer cases and reported a better clinical target volume (CTV) coverage with the robust plan with a setup error. 21 Wada et al used robust planning for patients with prostate cancer and reported improved CTV coverage at acceptable OAR doses, even with setup errors.…”
Section: Purposementioning
confidence: 99%
“…21 Wada et al used robust planning for patients with prostate cancer and reported improved CTV coverage at acceptable OAR doses, even with setup errors. 22 Therefore, robust planning can be considered a beneficial technique for making treatment plans robust against setup errors. We hypothesized that a PMRT treatment plan with IMRT that is robust against chest wall movement, including respiratory movement, can be created by setting the expected chest wall movement as the setup error during robust optimization.…”
Section: Purposementioning
confidence: 99%
See 2 more Smart Citations